The Effect of Music Intervention on Attention in Children: Experimental Evidence - Kasuya-Ueba, Yuka; Zhao, Shuo; Toichi, Motomi (Frontiers in Neuroscience, 2020)
Although music has been utilized as a therapeutic tool for children with cognitive impairments, how it improves children’s cognitive function remains poorly understood. As a first step toward understanding music’s effectiveness and to assess cognitive function improvement, we focused on attention, which plays an important role in cognitive development, and examined the effect of a music intervention on children’s attention. Thirty-five children, aged six to nine years, participated in this study, with data from 29 of the children being included in the analysis. A single 30-minute interactive music intervention was compared with a single 30-minute interactive video game intervention accompanied by computer-generated background music using a within-subjects repeated-measures design. Each intervention was implemented individually. Participants completed a standardized attention assessment, the Test of Everyday Attention for Children, before and after both interventions to assess changes in their attentional skills. The results indicated significant improvement in attention control/switching following the music intervention after controlling for the children’s intellectual abilities, while no such changes were observed following the video game intervention. This study provides the first evidence that music interventions may be more effective than video game interventions to improve attention control in children, and furthers our understanding of the importance of music interventions for children with attention control problems.